Virtual Reality in Orthopedic Surgery Training - Hasan LK; Haratian A; Kim M; Bolia IK; Weber AE; Petrigliano FA (Advances in Medical Education and Practice, 2021)
Laith K Hasan, Aryan Haratian, Michael Kim, Ioanna K Bolia, Alexander E Weber, Frank A Petrigliano USC Epstein Family Center for Sports Medicine at Keck Medicine of USC, Los Angeles, CA, USACorrespondence: Frank A PetriglianoClinical Orthopaedic Surgery, Chief, USC Epstein Family Center for Sports Medicine at Keck Medicine of USC, 1520 San Pablo st#2000, Los Angeles, CA, 90033, USATel +1 310 403-0441Email fpetrigliano@gmail.comAbstract: One emerging technology with the potential to improve and further transform the field of orthopaedic surgery is virtual reality (VR). VR has been explored and used in many different specialties with clinical applications, such as psychiatric therapy, pain management, rehabilitation, and traumatic brain injury. Recent studies have suggested that the use of VR during the training of orthopaedic surgery residents produces similar or improved surgical performance by residents. This is an area where VR can provide a tremendous benefit to the field of orthopaedic surgery, as it offers a safe and accessible complement to orthopaedic surgical training outside of the operating room (OR) and without involving patients directly. This review will elucidate the current state of virtual reality use in the training of orthopaedic surgeons and highlight key benefits and challenges in its application as a training resource.Keywords: virtual reality, orthopaedic, surgery, medical education, training